ANALISA KANDUNGAN NITROGEN PADA LAHAN SETELAH PENANAMAN LEGUMINOSAE COVER CROP The Analysis of Nitrogen Element on Soil after Legume Cover Crop Planting - Nurlaila (JURNAL AGRIMENT, 2017)
The purpose of the research is to analyze element on soil after leguminosae cover crop, increase the nitrogencontent of the soil. The research to implemented at Kebun Percontohan and Soil and Water Laboratory atAgricultural Polytechnic state Samarinda for 4 (four) months. The treatment of this research is the planting withdifference Legume Cover Crop (LCC), 3 (three) level treatment are t0 : before LCC planting; t1 : plantingCalopogonium mucunoides (CM), t2 : planting Centrocema pubescent (CP). The sampel from land that has beenplanted with LCC are analyzed in Soil and Water at Agricultural Polytechnic state Samarinda.The result analysis isN content at t0 is 0,067 %; at t1 is 0,025% and at t2 is 0,017%. That is shows that total N on the soil after plantingtwo LCC is lower than the total N on the land where LCC is no planted, whereas the total N at t1 is almost equalto the total N at t2.